The Functional Role of Enhancing the Survival and Activity of Progenitor Cells During Stroke Recovery - Denize, Sebastien (Université d'Ottawa / University of Ottawa, 2020)
Following a stroke, there is a significant increase in the number of precursor cells (PCs) that migrate to the site of injury. Their functional significance, based on studies that ablate PCs, remains controversial. This thesis aims to determine if enhancing the survival of PCs, and/or optogenetically stimulating PCs, is sufficient to improve stroke recovery. After photothrombosis-induced stroke, tamoxifen was used to recombine the nestin-expressing PCs and their progeny in iBax-ChR2 mice: inducible Nestin CreERT2 mice that have a floxed Bax, pro-apoptotic gene, and a floxed channelrhodopsin (ChR2-YFP) which allows for the modulation of neural activity. Removal of the Bax gene results in a significantly increased number of PCs with a neuronal phenotype surrounding the infarct, in the absence of altering behavioral recovery. To test if enhancing the activation of PCs around the stroke site could alter recovery, iBax-ChR2 mice received daily optogenetic stimulation for 5 weeks. Interestingly, stimulation of PCs around the stroke site resulted in an increased rate of neuronal differentiation in WT-ChR2 mice but no behavioural improvements after stroke. These findings suggest that substantially increasing the neurogenic response following a stroke has no impact on behavioural recovery. Moreover, contrary to an increasing number of studies stimulating the cortex post-stroke, specifically activating PCs in the ipsilesional cortex does not alter recovery. The implications of these data are becoming increasingly relevant as stroke researchers are beginning to experiment with non-invasive stimulation and stem cell therapies for stroke survivors.
Keywords: Stroke Recovery; Adult Neurogenesis; Optogenetics